1998
DOI: 10.1056/nejm199804303381804
|View full text |Cite
|
Sign up to set email alerts
|

Interferon Gamma-1b Compared with Placebo in Metastatic Renal-Cell Carcinoma

Abstract: No difference in outcome was observed in patients with metastatic renal-cell carcinoma who were treated with interferon gamma-1b as compared with placebo. These results emphasize the necessity of testing the efficacy of immunomodulators in randomized studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
72
0
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 272 publications
(75 citation statements)
references
References 25 publications
1
72
0
2
Order By: Relevance
“…[ 23 ] IFN-γ plays a central role in various anti-proliferative, anti-viral, and immunomodulatory treatments [ 24,25 ] and has also been used for many years in clinics for the treatment of chronic granulomatous disease. [ 26 ] Recombinant IFN-γ expressed in Escherichia coli has been deemed a promising antitumor agent to inhibit the growth of breast cancer cells and melanoma cells, [ 27 ] and treat hepatocellular carcinoma (HCC) and metastatic renal-cell carcinoma. [ 26 ] Our fi ndings suggest that nPCG carriers could retain the long-term effects of the induced JAK/STAT and mitochondrial pathways of all three active anticancer agents, which can regulate tumor cell survival directly through the STAT5, STAT1, and p53 associated anti-/proapoptotic cascades, resulting in the apoptosis of tumor cells.…”
Section: Introductionmentioning
confidence: 99%
“…[ 23 ] IFN-γ plays a central role in various anti-proliferative, anti-viral, and immunomodulatory treatments [ 24,25 ] and has also been used for many years in clinics for the treatment of chronic granulomatous disease. [ 26 ] Recombinant IFN-γ expressed in Escherichia coli has been deemed a promising antitumor agent to inhibit the growth of breast cancer cells and melanoma cells, [ 27 ] and treat hepatocellular carcinoma (HCC) and metastatic renal-cell carcinoma. [ 26 ] Our fi ndings suggest that nPCG carriers could retain the long-term effects of the induced JAK/STAT and mitochondrial pathways of all three active anticancer agents, which can regulate tumor cell survival directly through the STAT5, STAT1, and p53 associated anti-/proapoptotic cascades, resulting in the apoptosis of tumor cells.…”
Section: Introductionmentioning
confidence: 99%
“…Recent literature provides evidence that neoplastic cells may be implantated into the skin through diagnostic or surgical procedures (Nilufer, 2011), Cutaneous manifestations of urological tumors carry a poor prognosis as they are associated with widespread visceral involvement. Retrospective studies looking at urological malilgnancies that metastasized to the skin demonstrated a median survival time of 8 months (Thomas, 2004;Gleave, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…IFN-γ monotherapy has been studied in phase II trials, with an overall response rate of 8% [9]. In a phase III study with low dose of IFN-γ, the response rate was only 4.4% [10]. The combination of IFN-γ with IFN-α or with IFN-β has not shown superiority in terms of response rate as compared to IFN-α or IFN-β alone [9].…”
Section: Discussionmentioning
confidence: 99%